Economic Value Added and Market Value Added Methods and Their Influence in Measuring the Financial Performance of Food and Beverage Companies Listed on the Indonesia Stock Exchange (BEI) - Rezki Anggreni; Asriani Hasan; amir, Amir (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to determine Economic Value Added and Market Value Added and their influence in measuring the financial performance of food and beverage companies listed on the Indonesian Stock Exchange (BEI) in 2020-2022. This research uses quantitative methods, the samples in this research were taken from the Indonesian Stock Exchange (BEI) from 20 Food and Beverage Sector Companies. This research data was obtained using secondary data. The results of the research are from data processed using SPSS 26 statistical calculations. Based on the results of the SPSS 26 output partially, the results of the Economic Value Added research have a significant positive influence on the financial performance of the food and beverage sector listed on the Indonesia Stock Exchange (BEI) and Market Value Added also has an influential effect. Significant Positive Impact on the Financial Performance of the Food and Beverage Sector on the Indonesian Stock Exchange (BEI)